Childbirth Narratives in the Canton of Ticino (Switzerland): Perceptions and Experiences of Mothers Who Gave Birth before and during COVID-19 - Lazzari, Laura (Journal of the Motherhood Initiative for Research and Community Involvement, 2023)
This article analyzes written and oral narratives of pregnancy, childbirth, and postpartum produced by women who gave birth before and during the COVID-19 pandemic in Italian-speaking Switzerland. By using textual analysis and qualitative descriptive research methodologies, I compare birth stories in two autobiographical essays published before the pandemic in 2018 and 2019 and twenty-three oral testimonies from women who birthed between March 2020 and March 2021. The aim of the exploratory study is to highlight the main elements that define positive and negative birth experiences to understand how better outcomes could be achieved in society and medical practice. The present article discusses preliminary results and addresses possible strategies to improve obstetrical and maternal care in the postpandemic period.